The Effect of Asian Parliamentary Debate to Hone Students’ Critical Thinking - Harefa, Iman Setia (JET (Journal of English Teaching), 2024)
Various studies have shown that critical thinking development is vital in language learning as it facilitates language acquisition, helps communication skills improvement, and boosts language proficiency. This study aims to investigate the potential impact of the APD technique on students' critical thinking skills development. Conducted in SMA Negeri 71 in Jakarta over a period of over 3 months data was collected through a pre-test and a post-test employing a critical thinking test called Watson-Glaser Test. The results indicated that APD has a significant effect on students' critical thinking abilities. The mean scores of the pre-test and post in the experimental group were 45.2 and 62.3 respectively while the mean pre-test and post-test scores in the control group were 40.56 and 52.1 respectively. The experimental group's critical thinking improved from a good level to an excellent level, while the control group's critical thinking improved from a good level to a very good level. Based on the findings, it was concluded that APD is beneficial in enhancing students' critical thinking skills.